HER Family Receptors are Important Theranostic Biomarkers for Cervical Cancer: Blocking Glucose Metabolism Enhances the Therapeutic Effect of HER Inhibitors - Martinho, Olga; Silva-Oliveira, Renato; Cury, Fernanda P.; Barbosa, Ana Martins; Granja, Sara; Evangelista, Adriane Feijo; Marques, Fabio; Miranda-Goncalves, Vera; Cardoso-Carneiro, Diana; Paula, Flavia E. de; Zanon, Maicon; Scapulatempo-Neto, Cristovam; et al. (Ivyspring Int Publ, 2017)
Persistent HPV infection alone is not sufficient for cervical cancer development, which requires additional molecular alterations for tumor progression and metastasis ultimately leading to a lethal disease. In this study, we performed a comprehensive analysis of HER family receptor alterations in cervical adenocarcinoma. We detected overexpression of HER protein, mainly HER2, which was an independent prognostic marker for these patients. By using in vitro and in vivo approaches, we provided evidence that HER inhibitors, allitinib and lapatinib, were effective in reducing cervical cancer aggressiveness. Furthermore, combination of these drugs with glucose uptake blockers could overcome the putative HIF1-a-mediated resistance to HER-targeted therapies. Thus, we propose that the use of HER inhibitors in association with glycolysis blockers can be a potentially effective treatment option for HER-positive cervical cancer patients.
Keywords: ErbB; EGFR; HER2; cervical cancer; prognosis; targeted therapy